2019
DOI: 10.1113/ep086845
|View full text |Cite
|
Sign up to set email alerts
|

Vascular responses to hypoxia are not impaired in obstructive sleep apnoea patients free of overt cardiovascular disease

Abstract: New Findings What is the central question of this study?Does treatment of obstructive sleep apnoea (OSA) with nocturnal oxygen or continuous positive airway pressure (CPAP) improve hypoxic vascular responses, which are reportedly impaired in OSA? What is the main finding and its importance?Cerebrovascular and cardiovascular hypoxic responses were not impaired in OSA patients free of overt cardiovascular disease and known risk factors, and were not altered by nocturnal oxygen or CPAP treatment. We conclude tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
0
5
0
1
Order By: Relevance
“…Both office and home blood pressure measurements were reported in one study [ 16 ], another study reported ambulatory blood pressure and 24-h mean blood pressure measurement [ 13 ], and the remaining studies reported office blood pressure only. Change in blood pressure following intervention was reported in two studies [ 15 , 16 ] and calculated for four more studies [ 11 13 , 17 ] from mean differences and pooled sd s.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both office and home blood pressure measurements were reported in one study [ 16 ], another study reported ambulatory blood pressure and 24-h mean blood pressure measurement [ 13 ], and the remaining studies reported office blood pressure only. Change in blood pressure following intervention was reported in two studies [ 15 , 16 ] and calculated for four more studies [ 11 13 , 17 ] from mean differences and pooled sd s.…”
Section: Resultsmentioning
confidence: 99%
“…1295 papers were identified with the primary literature search (figure 1). After abstract and full-text review, nine studies with a total of 502 participants were included in the analysis [11][12][13][14][15][16][17][18][19]. No study was excluded based on the risk of bias assessment (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…342 The occurrence and development of cardiovascular diseases can be induced by sympathetic excitation disorder, oxidative stress, inflammatory response, endothelial injury, abnormal glucose, and lipid metabolism caused by hypoxia. [343][344][345][346] HIF-1α is the primary controller of physiological and pathological hypoxia and is widely expressed in cardiovascular diseases. 141,216,347 Almost all genes related to hypoxia, including glucose transporter (GLUT), VEGF, glycolytic enzymes, cell survival factors, and cell surface receptors, are directly or indirectly regulated by HIF-1.…”
Section: Neoplastic Diseasesmentioning
confidence: 99%
“…Действительно, как показали A.E. Beaudin [55] и соавт., у больных с СОАС без диагностированных ССЗ и факторов риска со средним индексом массы тела 27-31 кг/м 2 не наблюдается долгосрочного положительного эффекта при СИПАП-терапии, но этих пациентов отличает нормальная сосудистая реакция на гипоксию. У коморбидных пациентов последствия СОАС без специфической терапии могут быть тяжелыми.…”
Section: ;36(1):58-65unclassified